PEMAAFAN OLEH KORBAN DAN/ATAU KELUARGA KORBAN TERHADAP PELAKU TINDAK PIDANA DITINJAU DARI HUKUM PIDANA ISLAM DAN RUU KUHP SEBAGAI PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN - Suplinta Ginting; Alvi Syahrin; Madiasa Ablisar; Muhammad Ekaputra (USU LAW JOURNAL, 2018)
ABSTRACT The role of a victim and/ or victim’s family in a penal court is merely a witness, they are never involved to determine how long a charge or sentence is handed down to the Perpetrator. A victim and/ or victim’s family often feel unjust that creates disbelief in the law. The results of the research show that forgiveness is recognized in Islamic Law as it is regulated in the Koran and Hadiths of The Prophet Mohammed; while in Indonesian Law, forgiveness is a part of the customary law and is stipulated in the Bill of the Penal Law Article 55 paragraph (1) letter j. Forgiveness is given in order to insure justice, legal certainty, to uphold the dignity and pride of the victim and/ or the victim’s family, to liberated the Perpetrator from guilt and to settle the conflict between the Perpetrator and the victim and/ or victim’s family. The formulation of forgiveness in the Islamic Penal Law can reduce and even can discharge the Perpetrator from the sentence, except in hudud crime (offenses against God); while in the Bill of the Penal Law, formulation of forgiveness is merely something to be considered by the judge in handing down a verdict.   Keywords: Forgiveness, Victim and/ or victim’s family, Islamic Penal Law, Bill of the Penal Law.